Bridging Worlds, Blazing Bridges: Understanding the Enticing Saga of ELF in ELT and Its Complicated Nexus - Andi Rusgandi, Muhammad; Laily Zen, Evynurul; Basthomi, Yazid (Ethical Lingua: Journal of Language Teaching and Literature, 2024)
To unpack the complexities that ELF undergoes within the current methodology of ELT, this study bears down to reveal the challenges of incorporating the two practices presented by the increasing stigma attached to the “correct” use of language. Through a thorough analysis of theories and previous studies, the books and articles that span the years 2020 to 2023 (previous studies) are chosen to explore and comprehend the theories to dismantle the common preconception that influences the integration of ELF into ELT, as well as the principles of ELF that educators should follow along with the framework supporting ELT. It explores how the resilience of current EFL in ELT practices is towards Western English norms and the consequent consequences for both teachers and students. As a result, due to the tendency that is firmly ingrained in the norms of Western English, which has an impact on learning resources and evaluation methods, a shift in the paradigm of ELT practices is needed to accommodate students’ different learning styles, cultural backgrounds, and linguistics origins to ensure that all students have an equal opportunity to learn. At the end of this review paper, suggestions for further research and the implications for policymakers of ELT and EFL English teachers regarding the issues have been made.